The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1259/bjr.74.886.740901
|View full text |Cite
|
Sign up to set email alerts
|

UltrasoundvsCT for the detection of ureteric stones in patients with renal colic

Abstract: The aim of our study was to compare the accuracy of non-contrast spiral CT with ultrasound (US) for the diagnosis of ureteral calculi in the evaluation of patients with acute flank pain. 62 consecutive patients with flank pain were examined with both CT and US over a period of 9 months. All patients were prospectively defined as either positive or negative for ureterolithiasis, based on follow-up evaluation. 43 of the 62 patients were confirmed as having ureteral calculi based on stone recovery or urological i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
105
4
11

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(131 citation statements)
references
References 11 publications
11
105
4
11
Order By: Relevance
“…If there was a suspicion of hydronephrosis, (Table 1) then they were re-examined after evacuation of the bladder. This was done to exclude the possibility of pseudohydronephrosis [2]. The proximal ureter was best visualised in a coronal oblique view, using the kidney as a window.…”
Section: Methodsmentioning
confidence: 99%
“…If there was a suspicion of hydronephrosis, (Table 1) then they were re-examined after evacuation of the bladder. This was done to exclude the possibility of pseudohydronephrosis [2]. The proximal ureter was best visualised in a coronal oblique view, using the kidney as a window.…”
Section: Methodsmentioning
confidence: 99%
“…Many authors reported that sonography has limited role in diagnosis of ureteral calculi, but these data were from the 1980s and 1990s and this opinion is conflicted by recent studies (10)(11)(12). There is a recent study that has reported the sensitivity and specificity of sonography, 93% and 95% respectively, by definite demonstration of lithiasis with new sonographic equipments and technologies (13).In our study, gray-scale ultrasound examination alone detected ureteral calculi in 65.4% of patients presented to ER with low specificity. The twinkling artifact was first described in 1996 by Rahmouni et al, as a sign generated by a highly reflective object that, despite being stationary, would generate a rapid alteration between red and blue when interrogated with color Doppler sonography (4).…”
Section: Discussionmentioning
confidence: 99%
“…However, a higher level of skill, knowledge and familiarity with US fi ndings is needed when the stones are not at the ureteral junctions, or whenever alternative diagnoses must be made. 9 Ultrasound is very sensitive in depicting the anatomical changes associated with obstruction of the collecting system. 17 Nonetheless, we found that the sensitivity of US was only 22% in comparison with NCT, which is inadequate for routine use.…”
Section: Ureterovesical 47%mentioning
confidence: 99%
“…[5][6][7][8] Transabdominal ultrasound (US) has the advantages of being universally available, not exposing the patient to radiation and being independent of kidney function. [9][10] Because of these advantages, US is preferred by referring clinicians for evaluating acute renal colic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation